Other women - Lau, Evelyn (Simon & Schuster, 1995)
A portrait of a young woman devastated by the power of first love, by the author of "`Fresh Girls' and Other Stories". Fiona is a young artist who falls for an older married man. Although erotically charged, the affair is never consummated, yet Fiona remains obsessed long after he has left her